1998
DOI: 10.1007/s003960050330
|View full text |Cite
|
Sign up to set email alerts
|

The versatile surface properties of poly(cyclopentadiene)-modified silica particles (PCPD-silica): XPS and electrokinetic studies

Abstract: Surface properties of poly(cyclopentadiene)-silica hybrid particles (PCPD-silica) were studied by means of XPS and electrokinetic measurements. The surfaces of PCPD-silica particles exhibit two different areas with different properties: bare silica holes and PCPD patches. The PCPD chains contain different functional groups such as alcohol and carbonyl groups that were identified by XPS. The PCPD chains are grafted covalently onto the silica surface via Si-O-C bonds created by the reaction of silanol groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…PEO has been found to be very suitable as a model polymer for this purpose 86) . PS and PMMA are weak HBA polymers where the HBA capacity is lower than those of the probe molecule 1 a, 2, or 3 87,88) . Consequently, adsorption of HBA polymers with b A 0.4 decrease the HBD capacity of the Aerosil 300m surface, which can be clearly measured by a bathochromic shift of the UV-Vis absorption of adsorbed 3 as surface polarity indicator 86) .…”
Section: Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…PEO has been found to be very suitable as a model polymer for this purpose 86) . PS and PMMA are weak HBA polymers where the HBA capacity is lower than those of the probe molecule 1 a, 2, or 3 87,88) . Consequently, adsorption of HBA polymers with b A 0.4 decrease the HBD capacity of the Aerosil 300m surface, which can be clearly measured by a bathochromic shift of the UV-Vis absorption of adsorbed 3 as surface polarity indicator 86) .…”
Section: Compositesmentioning
confidence: 99%
“…Consequently, adsorption of HBA polymers with b A 0.4 decrease the HBD capacity of the Aerosil 300m surface, which can be clearly measured by a bathochromic shift of the UV-Vis absorption of adsorbed 3 as surface polarity indicator 86) . Therefore the solvatochromic method seems only suitable for fairly strong HBA/HBD interations of the solvent/surface 27) or polymer/surface combinations 87,88) . Fig.…”
Section: Compositesmentioning
confidence: 99%
“…This indicates that separate grinding does not bring about a change in the Si electron density because of the absence of the partner that interacts with SiO . Simon et al reported that the binding energy for Si}O bonds shifted by approximately 1.5 eV to a lower binding energy in a poly(cyclopentadiene)}silica hybrid (27). Therefore, the shift strongly suggests formation of Si}O}C bridging bonds at the interface between IM and SiO .…”
Section: Charge Transfer At the Im/sio 2 Interfacementioning
confidence: 89%
“…7. In the spectrum of the physical mixture, C1s peaks from C}OH or C}O}C (286 eV), and C"O or COOH (289 eV) (27) are detected. We cannot distinguish whether the C1s peak at 286 eV is from the C}C or C}H bonds of the IM molecule.…”
Section: Charge Transfer At the Im/sio 2 Interfacementioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectra and X-ray photoelectroscopy spectroscopy (XPS) are widely used as analytical methods for investigating the functional group and elemental and chemical composition of solids (organic, mineral or metallic) [10,11]. Unlike other techniques, XPS detects all the elements in the periodic table, except hydrogen and helium, which have no core electrons.…”
Section: Introductionmentioning
confidence: 99%